Analisis Modifikasi Alur Kampas Ganda dan Clutch Housing CVT terhadap Torsi Mesin 110 Cc - Harjuna Wisam Wirayudha; Asrori Asrori (Jurnal Kendali Teknik dan Sains, 2025)
The automotive sector continues to demonstrate significant progress in line with innovations in various supporting components of motor vehicles. Motorcycles, which initially served only as a practical means of transportation, have now evolved into a lifestyle element and a popular activity among many communities. Along with the increasing demand from consumers for performance and efficiency, the development of transmission technology, particularly the Continuously Variable Transmission (CVT) system, has become an important aspect that requires serious attention. One of the key components in the CVT system is the double clutch lining and the clutch housing, which play a vital role in transferring torque and power from the engine to the driving wheel. The performance of these components directly affects acceleration, efficiency, and engine durability. Therefore, research on the design and modification patterns of the double clutch lining and clutch housing is essential to determine an optimal configuration. This study applies an experimental method using a 110 cc motorcycle as the test object. Several modification patterns were applied to the double clutch lining and clutch housing to examine their influence on vehicle performance. The testing process was carried out using a dynotest, which enables precise measurement of torque and power across different engine speeds. The data obtained from these tests are expected to provide a clear overview of the effect of modification patterns on the transmission performance of motorcycles. The findings of this research are expected to contribute significantly to the development of more efficient and optimal designs for double clutch linings and clutch housings. Furthermore, this study may serve as a valuable reference for the automotive industry as well as motorcycle modification communities in enhancing vehicle performance while maintaining efficiency and component durability. In this regard, innovations in CVT components hold great potential to support the advancement of two-wheeled transportation technology in the future.